THE ANALYSIS OF TEACHER CREATIVITY IN WRITING A KID SONG - Pertiwi, Shilvia Nita; Kurniawati, Leli; Rachmawati, Yeni (Prodi PGPAUD, 2021)
This study is motivated by the lack of teacher’s creativity in writing a kid song. A new song evidentially taught to children generally changes merely on the lyric of an existing melody or song. While this activity is carried out repeatedly, it will be boring for children. Therefore, the creativity of teacher is needed in writing a kid song. Accordingly, the atmosphere of music learning could be more enjoyable and attract children’s attention. This study aims to determine the creativity of teacher in writing a kid song based on three categories of creative products; novelty products, resolution products, elaboration and synthesis products. This study used a qualitative approach. The data collection technique carried out by using documentation studies was in the form of kid songs recording from four participant teachers in the RA Songwriting Competition in Bandung Regency. The result of this study shows three points. First, in terms of the novelty aspect, the songs written by the participants were based on their own ideas, instead of the imitations of other people’s works. It could hardly be seen from the specific characteristic of melody, rhythm, and lyric that was different from the existing works. Second, in terms of the resolution aspect, the songs written by the participants could be a solution of the existing problems in accordance with the needs of children. Third, in terms of elaboration and synthesis aspects, the song texts were very communicative, easy to comprehend, and apprehended by the children. As a recommendation, the written songs could be used as a model for delivering learning material in Early Childhood Education